Suitable Groundwater Management: Equity in the North Carolina Central Coastal Plain, U.S.A. - Klein, Wendy A. (East Carolina University, 2018)
The purpose of this research is to assess the success of a regulation based on aquifer conditions, while testing a new approach for groundwater assessment and management that incorporates equity. Equity is often synonymous with fairness. By assessing the success of a pre-existing regulation and applying equity to a new approach to management creation, water resources are viewed as a multi-faceted, interconnected system. Citing concerns of falling water levels, low well yields and salt water intrusion in the Cretaceous aquifers of eastern North Carolina, the North Carolina Department of Environmental Quality enacted a protective and rigorous management strategy. The strategy, based on observed water levels, adopted a single dimensional approach to address aquifer protection. Many stakeholders deemed this approach as an unfair and inequitable strategy that did not consider the multiple, often conflicting criteria involved with managing a shared natural resource. The perceived lack of equity created conflict and opposition to collaborative efforts to sustain the Cretaceous aquifers. Moving beyond the traditional groundwater management concepts of safe yield, sustainability, and resilience, this research incorporates equity into the evaluation, allocation and management of groundwater systems. Using the CCPCUA in eastern North Carolina, U.S.A. as a case study, an equitable groundwater management approach is assessed. Although many natural resource researchers recognize the value equity, the literature lacks a framework for groundwater equity. This research begins by exploring basic equity concepts and proposing an equity framework that is applicable for management. By applying social-psychological and socio-legal concepts, the research explores how equity can contribute to acceptable policy creation. Lastly, the research explores a multi-criteria decision analysis tool, Suitability Analysis, which identifies areas most suitable to withstand changes in management strategies. This allows for a comparison of the results of a management strategy based on the physical conditions of an aquifer to one based on equity. The research suggests that an approach to groundwater management based on equity criteria can: 1) contribute to policy development and policy strategies that stakeholders find transparent and acceptable, and 2) identify specific areas of suitability and vulnerability to changes in groundwater withdrawals. Thus, the inclusion of equity not only provides a framework for creating adaptive groundwater management strategies but contributes to sustainable aquifers and societies. This solution features early stakeholder involvement and multi-criteria assessments of the resource.
Keywords: Equity; Multi-criteria Decision Analysis, Stakeholder Engagement; Cretaceous Aquifers; Groundwater--North Carolina--Management; Water resources development--North Carolina--Management; Environmental policy--North Carolina--Decision making